Cross-validation of HIRDLS and COSMIC radio-occultation retrievals, particularly in relation to fine vertical structure - Barnett, J; Hepplewhite, C; Osprey, S; Gille, J; Khosravi, R (SPIE-INT SOC OPTICAL ENGINEERING, 2008)
The High Resolution Dynamics Limb Sounder (HIRDLS) instrument was launched oil the NASA Aura satellite in July 2004. HIRDLS is a joint project between the UK and USA, and is a mid-infrared limb emission sounder designed to measure the concentrations of trace species, Cloud and aerosol, and temperature and pressure variations in the Earth’s atmosphere front the upper troposphere to the mesophere. The instrument is intended to make measurements at both high vertical and horizontal spatial resolutions, but validating those measurements is difficult because few other measurements provide that vertical resolution sufficiently closely in time. However, the FOPMOSAT-3/COSMIC suite of radio occultation satellites that exploit the U.S. GPS transmitters to obtain high resolution (similar to 1 km) temperature profiles in the stratosphere does provide sufficient profiles nearly coincident with those from HIRDLS. Comparisons show a good degree intercorrelation between COSMIC and HIRDLS down to about 2 km resolution, with similar amplitudes for each, implying that HIRDLS and COSMIC are able to measure the same small scale features. The optical blockage that occurred within HIRDLS during launch does not seem to have affected this capability.